2006
DOI: 10.1021/la061380q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Capacitances of Well-Defined Carbon Surfaces

Abstract: Reported is the capacitive behavior of homogeneous and well-defined surfaces of pristine carbon nanofibers (CNFs) and surface-modified CNFs. The capacitances of the well-defined CNFs were measured with cyclic voltammetry to correlate the surface structure with capacitance. Among the studied pristine CNFs, the edge surfaces of platelet CNFs (PCNF) and herringbone CNFs were more effective in capacitive charging than the basal plane surface of tubular CNF by a factor of 3-5. Graphitization of PCNF (GPCNF) changed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 7 publications
5
83
0
Order By: Relevance
“…Notably, considerably higher values were recorded for herringbone and platelet CNFs, with open graphitic edges on their surface, compared to the tubular type, for which the basal planes are exposed to electrolyte ions. The results obtained are in line with the finding of Kim et al [18] that the edge surfaces of CNFs promote charge storage. Kim et al synthesized also a series of CNFs with different graphitic layers alignment.…”
Section: Porous Texture Of Cnfssupporting
confidence: 92%
See 4 more Smart Citations
“…Notably, considerably higher values were recorded for herringbone and platelet CNFs, with open graphitic edges on their surface, compared to the tubular type, for which the basal planes are exposed to electrolyte ions. The results obtained are in line with the finding of Kim et al [18] that the edge surfaces of CNFs promote charge storage. Kim et al synthesized also a series of CNFs with different graphitic layers alignment.…”
Section: Porous Texture Of Cnfssupporting
confidence: 92%
“…However, pure CNFs/CNTs as capacitor electrode materials can only supply relatively low capacitance values, i.e., from 5 to 30 F g -1 , due to their moderate surface area (up to 400 m 2 g -1 ) [18][19][20][21]. It has been reported that CNTs with structural defects exhibit the higher gravimetric capacitance than purified and defectfree ones [18,22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations